KLASTERISASI GIZI BURUK DAN STUNTING DI PROVINSI SUMATERA UTARA MENGGUNAKAN K-MEANS CLUSTERING - Silitonga, Agnes Irene; Zada Annuri Nabila; Cinta Rizkia Zahra Lubis; Nurdina Safitri; Haryadi (Universitas Methodist Indonesia, 2024)
The objective of this study is to map the priority areas for addressing malnutrition and stunting in the province of North Sumatra. The data used consists of malnourished children and the prevalence of stunting in the North Sumatra Province in 2023, which will be analyzed using K-Means Clustering. Based on the analysis results, the priority for addressing malnutrition in North Sumatra Province is in cluster 2, namely Batu Bara Regency and Medan City, with a centroid value of 63. Meanwhile, the priority for addressing stunting has been identified in cluster 0, which includes Karo Regency, Pakpak Bharat, Batu Bara, West Nias, and Padangsidempuan City, with a centroid value of 17.46. This research is expected to provide valuable information for stakeholders in formulating targeted policies and programs to address malnutrition and stunting in North Sumatra.